WiN-Reha—effectiveness and durability of effects of orthopedic rehabilitation programs and the study of psychological determinants of aftercare behaviors: a study protocol - Feil, Katharina; Fritsch, Julian; Weyland, Susanne; Rittmann, Lena-Marie; Schmidt, Detlef; Jekauc, Darko (Frontiers in Rehabilitation Sciences, 2024)
Background and aim: Rehabilitation programs have been shown to have a positive impact on patients' health and work ability. However, the durability of these effects and the extent to which patients alter their health behaviors remain underexplored. This study is divided into two parts; the first assesses the effectivity of rehabilitation programs for orthopedic patients and the durability of effects. The second part examines psychological determinants of aftercare health behaviors. Subjects and methods: Study Part 1 employs a longitudinal study design with up to nine measurement occasions encompassing a three-year follow-up period. Treatment is provided as per orthopedic indications through rehabilitation centers. Measures include subjective health, work ability, body weight, and physical activity behavior. Study Part 2 incorporates a mixedmethods design, involving both quantitative and qualitative assessments. The quantitative component aims to recruit a subsample from Study Part 1 to assess psychological determinants of aftercare health behaviors over 12 to 24 weeks using Ambulatory Assessment. The qualitative component aims to explore the reasons for maintenance and discontinuation of health behaviors and involves a reflexive thematic analysis of interviews with at least 16 individuals, analyzing the differences between those who adopt and those who discontinue their aftercare health behavior. Discussion: This comprehensive research project may offer insights into the long-term effectivity of rehabilitation programs. Furthermore, it may foster a more profound understanding of the successful incorporation of health-promoting aftercare behaviors, such as physical activity, into everyday life. Therefore, this study may contribute significantly to the evolving field of patient-centered rehabilitation.